A preliminary study of cloud clusters in the near-equatorial regions of south Indian Ocean during southwest monsoon season - MISHRA, D. K.; PRASAD , ONKARI; JAIN, R. K. (MAUSAM, 2022)
The occurrence, characteristics and movement of cloud clusters within the latitude belt equator to l5oS over the Indian Ocean during the period 1 May to 31 July 1973 have been studied in this paper, utilizing the daytime visible channel satellite cloud imagery received from NOAA-2 spacecraft. It is found that cloud clusters mainly occur east of latitude 60oE and that their number generally increases from west to east. They have the maximum frequency of Occurrence in the latitude belt equator to 50S. The cloud clusters are predominantly amorphous in shape, indicating that mostly weak low pressure systems occur in this region. Their lire period ranges upto 8 days but most of them have a life period of less than 2 days. A majority of those having a life period of 2 days or more show a westward or northwestward movement, with a tendency to recurve northeastward subsequemly, as theyapproach the equator.